2017
DOI: 10.3390/toxins9030085
|View full text |Cite
|
Sign up to set email alerts
|

Do Plant-Bound Masked Mycotoxins Contribute to Toxicity?

Abstract: Masked mycotoxins are plant metabolites of mycotoxins which co-contaminate common cereal crops. Since their discovery, the question has arisen if they contribute to toxicity either directly or indirectly through the release of the parent mycotoxins. Research in this field is rapidly emerging and the aim of this review is to summarize the latest knowledge on the fate of masked mycotoxins upon ingestion. Fusarium mycotoxins are the most prevalent masked mycotoxins and evidence is mounting that DON3Glc and possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…Masked mycotoxins refer to plant derivatives of fungal mycotoxins. There is concern and data to support that these hybrid molecules can contribute to toxicity either directly or indirectly through the release of the parent mycotoxin in animal digestive tracks [107]. Research groups worldwide Fig.…”
Section: The Janus Face Of Filamentous Fungimentioning
confidence: 99%
“…Masked mycotoxins refer to plant derivatives of fungal mycotoxins. There is concern and data to support that these hybrid molecules can contribute to toxicity either directly or indirectly through the release of the parent mycotoxin in animal digestive tracks [107]. Research groups worldwide Fig.…”
Section: The Janus Face Of Filamentous Fungimentioning
confidence: 99%
“…The metabolic burden is also higher when several toxins are found in the same feed (Milićević et al 2010;Alshannaq and Yu 2017). With mass-based methods, the analysis of masked toxins (Berthiller et al 2013;Gratz 2017) and metabolites (Warth et al 2012;Streit et al 2013;Abdallah et al 2017) in the feed is a real possibility. Furthermore, mycotoxin secondary product analysis in other related matrices food matrices is promising (Escrivá et al 2017).…”
Section: Mycotoxin Co-occurrencementioning
confidence: 99%
“…The THs, which are tetracyclic sesquiterpenes with an epoxy-ring [12,14], are divided into type A consisting of T-2 and HT-2 toxins and type B with deoxynivalenol (DON) and nivalenol (NIV), the most important representatives [12]. Zearalenone (ZEA) and its hydroxylated derivatives α-and β-zearalenone (α-ZEA and β-ZEA) are lactone derivatives commonly found in food commodities [15]. It has been reported that ZEA usually co-occurs with one or more of the THs, because of the ability of its producing fungi to synthesize more than one mycotoxin [16].…”
Section: Common Mycotoxins In Africamentioning
confidence: 99%